2018
DOI: 10.1039/c8ta08384c
|View full text |Cite
|
Sign up to set email alerts
|

Direct storage of holes in ultrathin Ni(OH)2 on Fe2O3 photoelectrodes for integrated solar charging battery-type supercapacitors

Abstract: A water oxidation side reaction on a photoelectrochemical charging supercapacitor is completely suppressed by controlling the thickness of a capacitive material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…The photocurrent decays quickly and negligible steady photocurrent is obtained at all selected potentials. According to previous studies (Wang et al, 2013;Zhu et al, 2018), the transient photocurrent comes from Ni(OH) 2 oxidation and the photocurrent will disappear once all of Ni(OH) 2 is oxidized into NiOOH. The steady photocurrent comes from water oxidation.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The photocurrent decays quickly and negligible steady photocurrent is obtained at all selected potentials. According to previous studies (Wang et al, 2013;Zhu et al, 2018), the transient photocurrent comes from Ni(OH) 2 oxidation and the photocurrent will disappear once all of Ni(OH) 2 is oxidized into NiOOH. The steady photocurrent comes from water oxidation.…”
Section: Resultsmentioning
confidence: 88%
“…Therefore, Faradaic layers are more ideal than non-Faradaic layers for high-efficiency solar water-splitting cells. However, other reports suggested that the coating of Faradaic layers on semiconductor photoanodes decreased the performance of solar water splitting (Wang et al, 2013;Lim et al, 2017;Zhu et al, 2018). Since both the semiconductors and the Faradaic layers are the same (Liu et al, 2016;Young and Hamann, 2014;Steier et al, 2015), the inconsistent results in previous studies possibly originate from uncontrollable interface structures between semiconductors and Faradaic layers.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…[ 65 ] Compared with TiO 2 , the higher VB of Fe 2 O 3 with thicker Ni(OH) 2 was demonstrated to effectively inhibit water oxidation. [ 66 ] After inhibiting water oxidation, the Fe 2 O 3 @ Ni(OH) 2 based photocapacitors exhibited a specific capacitance of 20.6 mF cm −2 at a discharge current density of 0.1 mA cm −2 .…”
Section: Photorechargeable Supercapacitorsmentioning
confidence: 99%